2017
DOI: 10.1016/j.berh.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of the autonomic nervous system in osteoarthritis

Abstract: a b s t r a c tJoint homeostasis is affected by local and systemic processes. Catecholaminergic and cholinergic fibers innervate the synovium, trabecular bone, and periosteum. Several studies have investigated the involvement of the autonomic nervous system (ANS) in joint homeostasis and the pathophysiology of osteoarthritis (OA). Various resident cells of osteoarticular tissues express receptors for sympathetic and parasympathetic neurotransmitters (norepinephrine/epinephrine and acetylcholine, respectively),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 81 publications
0
30
0
Order By: Relevance
“…nicotinic Ach and muscarinic receptors expressed by resident cells of the bone to exert anti-inflammatory effects, we wondered whether cholinergic nerves are locally expressed in subchondral bone 10,11 . Because it is challenging to characterize nerve structures using two-dimensional (2D) techniques with confocal microscopy, we adapted a recently published protocol for the three-dimensional (3D) analysis of immunofluorescence 12,13 .…”
mentioning
confidence: 99%
“…nicotinic Ach and muscarinic receptors expressed by resident cells of the bone to exert anti-inflammatory effects, we wondered whether cholinergic nerves are locally expressed in subchondral bone 10,11 . Because it is challenging to characterize nerve structures using two-dimensional (2D) techniques with confocal microscopy, we adapted a recently published protocol for the three-dimensional (3D) analysis of immunofluorescence 12,13 .…”
mentioning
confidence: 99%
“…Our understanding of the role of the non-neuronal cholinergic system as a critical regulator of inflammation and immunity is growing but remains controversial and poorly investigated in OA pathophysiology (21,22). Here, we showed that human and murine chondrocytes are part of the non-neuronal cholinergic system allowing local autocrine/paracrine action of ACh on joint cells.…”
Section: Discussionmentioning
confidence: 89%
“…69 Moreover, the choline acetyltransferase (ChAT) is detected in OA synovium, which means that resident cells are capable of synthesizing and releasing ACh in situ without autonomic innervation. 68,70 These data suggest that CAP may act on OA simultaneously through the vagus nerve and ACh, and then play a role in inhibiting OA development.…”
Section: The Cap and Osteoarthritismentioning
confidence: 87%
“…67 Studies have observed that the autonomic nervous system (ANS) is involved in joint homeostasis and OA pathogenesis: the subchondral bone of OA patients has peripheral and cholinergic fibres, which innervate the synovium, trabecular bone and periosteum; and resident cells of osteoarticular tissue have receptors for ACh as chondrocytes express α7nAChR on their surfaces. 63,68,69 α7nAChR was detected in chondrocytes of OA patients, but the increased expression was not as significant as that of patients with RA; meanwhile, mRNA expression of CHRFAM7A-which is capable of pruning α7nAChR and associated with the cartilage degradation--was significantly higher than that of Chrna7, indicating that functions of the CAP are impaired in OA, and this hypothesis was confirmed as prognosis of Chrna7 −/− mice that underwent meniscectomy was observably lower than that of normal control mice that got the same operation. 69 Moreover, the choline acetyltransferase (ChAT) is detected in OA synovium, which means that resident cells are capable of synthesizing and releasing ACh in situ without autonomic innervation.…”
Section: The Cap and Osteoarthritismentioning
confidence: 99%